THE ROLE OF NATIONAL HUMAN RIGHTS COMMISSION IN PREVENTING TRAFFICKING WOMEN AND CHILDREN IN INDIA-A STUDY - T.S.Shyam Prasad (INTERNATIONAL JOURNAL OF POLITICAL SCIENCE (IJPSC), 2024)
Trafficking in women and children, both male and female, is a grave violation of several human rights. Given the existing trafficking scenario in India and as a follow-up of a recommendation made by the Asia Pacific Forum of National Human Rights Institutions in a meeting held in Manila in September 1999, the then United Nations High Commissioner for Human Rights had requested each National Institution in the region to nominate an appropriate individual to serve as a Focal Point on Human Rights of Women, including Trafficking. Accordingly, in the year 2001, the National Human Rights Commission designated one of its Members to serve as the Focal Point on Human Rights of Women, including Trafficking. The Focal Point undertook several activities, which included an Action Research on Trafficking in Women and Children in India and a National Workshop to Review the Implementation of Laws and Policies Related to Trafficking: Towards an Effective Rescue and Post-Rescue Strategy. Both the Report of the Action Research on Trafficking in Women and Children in India, that was conducted by the National Human Rights Commission in collaboration with UNIFEM and the Institute of Social Sciences and the Report of the National Workshop to Review the Implementation of Laws and Policies Related to Trafficking: Towards an Effective Rescue and Post-Rescue Strategy, that was conducted by the Commission in collaboration with PRAYAS, a field Action Project of the Tata Institute of Social Sciences, Mumbai have made a number of recommendations and suggestions whereby trafficking in women and children could be prevented and combated. These Reports were released to the public in August, 2004. Copies of both the Reports were forwarded to concerned officials in all the States/Union Territories for compliance. So far, very few States have reported back to the Commission with regard to the action taken by them. In order that these recommendations and suggestions are implemented in true spirit, the Commission is of the view that it is necessary to have a comprehensive Plan of Action (PoA) to prevent and end trafficking in women and children.